THE CLINOPYROXENE BAROMETRY OF MANTLE PERIDOTITES: IMPLICATION FOR DIAMOND EVALUATION POTENTIAL - Simakov S.K. (My University, 2001)
The pyroxene thermometer is based on the following reaction: (orthoenstatite in Opx ss)=(clinoenstatite in Cpx ss). The accuracy of the thermometer assessed by peridotitic mineral assemblages obtained from experiments in the range of 1050–1755°C and 20–60 kbar (46 analyses, in total) was as follows: 1σ= 54° and Δ(mean) = 46°C. The optimum range of application of the thermometer is T= 1100 –1500°C and P= 25–50 kbar. The model was used for the estimation of the PT parameters related to the formation of diamond-bearing and barren peridotite xenoliths from Yakutian and South African kimberlite. The results obtained indicate that the elaborated modification of the thermometer allows one to estimate the formation temperature of deep clinopyroxene xenocrysts. It fits the petrological criteria and may be applied to the estimation of the diamond potential of mantle-derived rocks.